On the Reinforcement of the Liapunov Theorem - Paulauskas, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Паулаускас. Об одном усилении теоремы ЛяпуноваV. Paulauskas. Apie Liapunovo teoremos sustiprinimą